The morphology of Corneal Endothelium with the wear of hydrogel color contact lenses prescribed by unlicensed vendors / Siti Afifah Md Nor - Md Nor, Siti Afifah (2015)
Purpose: To compare the morphology of corneal endothelium following wear of hydrogel cosmetic color contact lenses (CCL) prescribed by unlicensed vendors and authorized eye clinician. Materials and methods: Eleven research subjects who wear CCL acquired from unlicensed vendors and another eleven regular patients of Contact Lens Clinic, UiTM Puncak Alam were invited to participate in this study. All subjects were female Malays with the age range of 21 to 25 years old. The participants were assessed with preliminary routine procedures prior to endothelial photography using Tomey EM-3000 non-contact specular microscope without wearing contact lenses. The output endothelial morphological parameters were endothelial cell density (ECD), coefficient of variation (CV) and percentage of cell hexagonality. Independent-samples t-test and Mann-Whitney U test were used to verify the mean difference of the endothelial morphological parameters. Pearson’s product-moment correlation was used to determine the association of endothelial morphological changes with the duration of consuming CCL. Results: There was no clinically significant difference of corneal endothelial morphology between wearers who obtained CCL from unlicensed vendors and prescribed by authorized eye clinician. ECD of experimental group was 2879.82 ± 199.40 cell/mm2 whilst control group was 2956.09 ± 215.93 cell/mm2 . The difference of -76.27 (95% CI, -261.13 to 108.58) cell/mm2 , t(20) = -0.86, p = 0.589 was not a statistically significant. The CV were 38.18 ± 5.50% and 37.09 ± 4.30% for experimental and control group respectively. The difference of 1.09 (95% CI, -3.29 to 5.47), t(20) = 0.520, p = 0.422 was also not significant. The percentage of cell hexagonality was not statistically significant with mean rank of experimental and control group of 10.36 and 12.64 respectively, U = 48, z = -0.822, p = 0.438. There was a small positive correlation between duration of consuming CCL with ECD changes (p = 0.46) and CV (p = 0.44). Conclusion: CCL wear would induce endothelial morphological changes, regardless of the sources of CCL supply. Despite the known effects of long duration of soft contact lens use on corneal endothelial cell morphology, this study could not draw a significant correlation between them.